2011
DOI: 10.1007/s10974-011-9261-x
|View full text |Cite
|
Sign up to set email alerts
|

Protein phosphatase 2A affects myofilament contractility in non-failing but not in failing human myocardium

Abstract: Protein phosphatase (PP) type 2A is a multifunctional serine/threonine phosphatase that is involved in cardiac excitation–contraction coupling. The PP2A core enzyme is a dimer, consisting of a catalytic C and a scaffolding A subunit, which is targeted to several cardiac proteins by a regulatory B subunit. At present, it is controversial whether PP2A and its subunits play a critical role in end-stage human heart failure. Here we report that the application of purified PP2AC significantly increased the Ca2+-sens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
43
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 52 publications
(67 reference statements)
5
43
0
Order By: Relevance
“…For example, separate studies using epicardial biopsies [10] and samples from unspecified regions of the heart [11] have shown that isometric force is reduced by ~80% in patients with heart failure. Other works, using samples from unspecified regions of the left ventricle, suggests that there is no significant effect of heart failure on maximum isometric force [12][13][14]. In the present experiments, heart failure reduced the average force generated by the experimental preparations (Figure 2, p=0.042).…”
Section: Region-specific Modifications In Systolic Functionsupporting
confidence: 47%
See 1 more Smart Citation
“…For example, separate studies using epicardial biopsies [10] and samples from unspecified regions of the heart [11] have shown that isometric force is reduced by ~80% in patients with heart failure. Other works, using samples from unspecified regions of the left ventricle, suggests that there is no significant effect of heart failure on maximum isometric force [12][13][14]. In the present experiments, heart failure reduced the average force generated by the experimental preparations (Figure 2, p=0.042).…”
Section: Region-specific Modifications In Systolic Functionsupporting
confidence: 47%
“…Other groups have shown that cTnI phosphorylation can also influence Ca 2+ sensitivity [12,23]. In this study, site-specific cTnI phosphorylation was reduced in heart failure samples at Ser23/24 ( Figure S5, p=0.012) but there was not a significant relationship between this parameter and pCa 50 (r=0.034, p=0.850, data not shown).…”
Section: Region-specific Modification In Ca 2+ Sensitivitymentioning
confidence: 47%
“…PP2A induced uniform dephosphorylation of cTnI in preparations previously treated with both PKA and PKC (38). We have recently demonstrated that the administration of purified PP2A C dephosphorylated cTnI at PKA sites Ser 23/24 , resulting in an increased Ca 2ϩ sensitivity of the contractile apparatus in isolated skinned human cardiomyocytes (39). A decreased cTnI phosphorylation at PKA-dependent phosphosites was also found in a dog heart failure model (40).…”
Section: Discussionmentioning
confidence: 84%
“…In myocytes, PP2A activity is linked with multiple targets important in membrane excitability and excitation-contraction coupling including the ryanodine receptor (RyR2), connexin43, Ca v 1.2, troponin, Na ϩ /Ca 2ϩ exchanger (NCX), and phospholamban (16 -22). Although manipulation of PP2A activity or expression in animal or cell models produces defects in myocyte physiology and cardiac phenotypes (19,20,(23)(24)(25)(26), the role and regulation of this critical enzyme family in cardiovascular disease is still largely elusive. In fact, we lack even a basic fundamental understanding of the expression, activity, and regulation of protein phosphatases in heart and/or in cardiovascular disease.…”
mentioning
confidence: 99%